Enabling a Durable Electrochemical Interface via an Artificial Amorphous Cathode Electrolyte Interphase for Hybrid Solid/Liquid Lithium‐Metal Batteries. (27th February 2020) - Liang, Jia‐Yan; Zhang, Xu‐Dong; Zeng, Xian‐Xiang; Yan, Min; Yin, Ya‐Xia; Xin, Sen; Wang, Wen‐Peng; Wu, Xiong‐Wei; Shi, Ji‐Lei; Wan, Li‐Jun; Guo, Yu‐Guo
Abstract: A hybrid solid/liquid electrolyte with superior security facilitates the implementation of high‐energy‐density storage devices, but it suffers from inferior chemical compatibility with cathodes. Herein, an optimal lithium difluoro(oxalato)borate salt was introduced to build in situ an amorphous cathode electrolyte interphase (CEI) between Ni‐rich cathodes and hybrid electrolyte. The CEI preserves the surface structure with high compatibility, leading to enhanced interfacial stability. Meanwhile, the space‐charge layer can be prominently mitigated at the solid/solid interface via harmonized chemical potentials, acquiring promoted interfacial dynamics as revealed by COMSOL simulation. Consequently, the amorphous CEI integrates the bifunctionality to provide an excellent cycling stability, high Coulombic efficiency, and favorable rate capability in high‐voltage Li‐metal batteries, innovating the design philosophy of functional CEI strategy for future high‐energy‐density batteries. Abstract : An der Grenze : Eine amorphe Kathoden‐Elektrolyt‐Interphase (CEI) mit überragender chemischer Kompatibilität wurde durch die In‐situ‐Umwandlung von LiDFOB gebildet. Sie stattet Fest/flüssig‐ Hochspannungsbatterien mit deutlich erhöhter Grenzflächenstabilität, Langlebigkeit und Dynamik aus.